2021
DOI: 10.1039/d1cy00238d
|View full text |Cite
|
Sign up to set email alerts
|

Heterodinuclear catalysts Zn(ii)/M and Mg(ii)/M, where M = Na(i), Ca(ii) or Cd(ii), for phthalic anhydride/cyclohexene oxide ring opening copolymerisation

Abstract: A series of heterodinuclear catalysts, coordinated by a Schiff base ligand, for ring opening copolymerisation of phthalic anhydride/cyclohexene oxide, highlight the best metal combinations for fast and selective catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
(149 reference statements)
0
19
0
Order By: Relevance
“…Because phthalic anhydride/CHO ROCOP is a more commonly used monomer, catalyst 5 was also tested using it under otherwise equivalent conditions ([Cat] 0 :[PA] 0 :[CHO] 0 =1 : 100 : 2000, 0.05 mol%, 100 °C). Catalyst 5 performs well compared to other dinuclear catalysts, such as [( o ‐van)Zn(II) 2 (OAc) 2 (TOF=198 h −1 , 0.125 mol%, 100 °C) and to Zn(II)Mg(II) catalysts [21,54] . Although catalyst 5 showed slightly higher activity compared with [( o ‐van)Al(III)K(I)(OAc) 2 ] for NA/CHO ROCOP, it underperforms against this same catalyst for PA/CHO with the Al(III) catalyst showing very high activities (TOF=1072 h −1 , 0.05 mol%, 100 °C) [53] .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Because phthalic anhydride/CHO ROCOP is a more commonly used monomer, catalyst 5 was also tested using it under otherwise equivalent conditions ([Cat] 0 :[PA] 0 :[CHO] 0 =1 : 100 : 2000, 0.05 mol%, 100 °C). Catalyst 5 performs well compared to other dinuclear catalysts, such as [( o ‐van)Zn(II) 2 (OAc) 2 (TOF=198 h −1 , 0.125 mol%, 100 °C) and to Zn(II)Mg(II) catalysts [21,54] . Although catalyst 5 showed slightly higher activity compared with [( o ‐van)Al(III)K(I)(OAc) 2 ] for NA/CHO ROCOP, it underperforms against this same catalyst for PA/CHO with the Al(III) catalyst showing very high activities (TOF=1072 h −1 , 0.05 mol%, 100 °C) [53] .…”
Section: Resultsmentioning
confidence: 93%
“…For example, complexes of the same macrocycle coordinated to Zn(II)M, where M=Li(I), Na(I), K(I), Ca(II), Al(III), Ga(III) or In(III), were all much less active than the Zn(II)Zn(II) species [20] . A dinucleating Schiff base ligand derived from o ‐vanillin, also afforded catalysts showing similar reactivity trends Zn(II)Zn(II)>Zn(II)Ca(II)>Zn(II)Cd(II)≫Zn(II)Na(I) [21] . This prior work indicates that heterodinuclear combinations of Zn(II) with Group 1–3 metals are not synergic and, even in the case of Zn(II)Mg(II) complexes catalytic synergy depends upon the ancillary ligand and coordination chemistry.…”
Section: Introductionmentioning
confidence: 98%
“…[17] Williams et al introduced heteroleptic bimetallic Mg and Zn complexes, which showed excellent catalytic activity and selectivity in the ROCOP of cyclic anhydrides and epoxide even in the absence of any nucleophilic co-catalysts. [18][19][20][21] Since then, active zinc, [22,23] magnesium, [24][25][26] iron, [27] chromium, [28] cobalt, [29,30] aluminum [31] and manganese complexes [32] were reported, with the cobalt and chromium complexes showing very high activities and regioselectivities in the epoxide-anhydride ROCOP. [33] Binuclear complexes showed far higher catalytic activities than mononuclear species, [34,35] indicating a bimetallic reaction mechanism in homopolymerization of epoxides [36] and copolymerization of epoxide and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Heteronuclear cooperativity has emerged as an important catalyst design concept and allows for improvement of activity beyond values achievable for homo-multinuclear metal catalysts. , In polymerization catalysis, hetero-multinuclear complexes show a real promise in lactone ring-opening polymerizations (ROP), olefin polymerizations and relevant to this work, the ring-opening copolymerizations (ROCOP) of CO 2 or organic anhydrides with epoxides. However, not all metal combinations work equally well as some fail to act synergically and, consequently, better understanding of the phenomena underpinning catalysis is needed. One important open question is whether heteronuclear cooperative catalysts show the same degree of synergy when changing the substrate, for example, from CO 2 to anhydride in ROCOP catalysis. Another series of questions concern how conventional ligand design and modification strategies affect internuclear cooperativity.…”
Section: Introductionmentioning
confidence: 99%